A Study on Reducing Heat Gains through the use of Green Envelope - Alabadla, Mania (2013)
The increment of ambient temperature in urban areas caused by heat island phenomenon increases the stress on cooling loads and increases the electricity peak demand. 75% of electricity consumption in Abu Dhabi is used for cooling the buildings which increase the carbon footprint of UAE significantly. The rising anxiety of climate change and the importance of energy resources, led to the creation of Estidama rating system by the government of Abu Dhabi in order to promote green buildings that incorporate green roofs and green facades. This dissertation focuses on evaluating the thermal behaviors of green envelope (green roofs and green facades) on the buildings cooling loads and the overall energy consumption. The software that been used to investigate the performance of green roofs and living walls is the IES Virtual Environment (VE). IES is a thermal load and energy analysis simulation program, to find out the end user`s annual energy of five cases were modeled. The first model is the base case which is the building with conventional facades and conventional roof while the other cases are for green roofs with different thickness and living wall case and finally a case for the combination of green roof and living wall. Green roofs can contribute in reducing building`s cooling load however this reduction is varying from the whole building load and the last floor load at a high rise building that is consisting from sixteenth floors which make installing green roofs in low rise buildings more efficient than high rise buildings unless combined with living walls. The usage of green roof and living walls in high rise building reduced the cooling loads by 24.35% comparing to the base case. The energy use of the whole building dropped by 23% compared to the base case while the CO2 emissions dropped by 17%. Irrigation approach was to treat grey water resulted from the building and use it to irrigate green areas within the building itself. It was important to find out that the irrigation water demand compromising 55.7 % of the overall treated grey water that been generated within the building .This low percentage enables the use of the extra treated water in other activities which can compensate the capital cost of grey water treatment systems .